Applying a glowworm swarm algorithm for optimising the assembly sequence of a car engine pump valve - Alharbi, Fawaz; Wang, Qian (2018 International Conference on Electronics, Control, Optimization and Computer Science (ICECOCS), 2018)
When assembling a product, assembly sequence is subject to the inherent nature of assembly components as well as the number of assembly components that may also increase complexity of assembly process. Additionally, assembly efficiency relies on reduction of assembly time that is partially affected by determination of an optimal assembly sequence of a product. A study through a literature review shows that the glowworm swarm optimisation algorithm (GSOA) can be possibly useful for solving assembly sequence optimisation problems. This paper presents an investigation into a GSOA used for solving an assembly sequence problem of a car engine pump valve. The study demonstrates that the GSOA can provide a quick solution in obtaining an optimal or near-optimal assembly sequence of the assembled product that is manufactured in a small-sized company.